Analisis Yuridis Penerapan Asas Prejudiciel Geschill dalam Perkara Publik dan Privat - Maulana Syekh Yusuf; Hilman Prayuda; Imam Alfurqan (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
Legal disputes involving simultaneous criminal and civil dimensions often raise complex juridical issues, particularly in the context of business transactions. One relevant concept to address this issue is the prejudiciel geschill, a doctrine originating from Dutch law that regulates pre-judicial disputes as a condition for the suspension of criminal proceedings. This study aims to analyze the dispute resolution mechanism of prejudiciel geschill in criminal fraud cases and breach of contract, as well as to examine the judges' considerations in Civil Decision Number 1075/Pdt.G/2019/PN Sby and Criminal Decision Number 2482/Pid.B/2020/PN Sby. The research method used is normative juridical with a statutory and case approach. The results indicate that the application of prejudiciel geschill in both decisions reflects the interplay between civil and criminal judgments in the Indonesian judicial system. The Panel of Judges of the Surabaya District Court applied Supreme Court Regulation Number 1 of 1956 and SEMA Number 4 of 1980 as the basis for suspending criminal proceedings pending the final civil court decision. The study concludes that the concept of prejudiciel geschill plays a strategic role in preventing jurisdictional overlaps and ensuring legal certainty. A more comprehensive statutory regulation within national criminal procedural law is needed to accommodate the consistent application of this principle.